2000
DOI: 10.1007/s004200050018
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic DNA adducts in coke-oven workers, in relation to exposure, lifestyle and genetic polymorphism of metabolic enzymes

Abstract: Effects of several variables, such as smoking, genetic polymorphism of 2 CYP1A1, NAT2, and gene p53, and a family history of cancer on DNA adduct levels were found, suggesting that these variables should be considered when evaluating the genotoxic effect of occupational exposure to PAHs using WBCs DNA adducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…However, the results thus far are inconsistent for the effects of glutathione S-transferase polymorphisms on exposure biomarkers in coke-oven workers. For instance, the GSTM1 null genotype was found to be associated with increased levels of benzo(a)pyrene diol epoxide -DNA adducts among the coke-oven workers (21,22), but this association was not confirmed by other studies (23)(24)(25).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the results thus far are inconsistent for the effects of glutathione S-transferase polymorphisms on exposure biomarkers in coke-oven workers. For instance, the GSTM1 null genotype was found to be associated with increased levels of benzo(a)pyrene diol epoxide -DNA adducts among the coke-oven workers (21,22), but this association was not confirmed by other studies (23)(24)(25).…”
Section: Introductionmentioning
confidence: 58%
“…Although it is well known that GSTM1 can detoxify reactive metabolites of benzo(a)pyrene and other PAHs (38), and that the homozygous deletion of GSTM1 leads to the loss of GSTM1 functions (17), several studies have shown that the coke-oven workers without the GSTM1 allele did not have a higher risk of having high benzo(a)pyrene diol epoxide -DNA adduct levels compared with individuals with the GSTM1 non -null genotype (23)(24)(25). In the present study, it was found that this GSTM1 polymorphism was not associated with the levels of DNA damage in the coke-oven workers.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, most previous studies measured urinary and/or blood biomarkers at the end of a work shift as a single measurement (5,7,26,32,33). These readings may be affected by the known circadian variation in certain biomarker level (e.g., 8-oxodG; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that these variants are associated with DNA adduct levels in lymphocytes of subjects occupationally exposed to PAHs. [32][33][34] One study suggests that the m1 variant affects oestrogen metabolism.…”
mentioning
confidence: 99%
“…The functional effects of the other variants are summarized in Table I. [26][27][28][29][30][31][32][33][34][35][36][37] As the presence of the CYP1A1*2A (m1) and CYP1A1*2C (m2) variants appear to be associated with higher levels of biomarkers for PAH exposure, it might be expected that the m1 and m2 variants would be associated with an increased risk for colorectal cancer. However, the results of previous studies of colorectal neoplasia and the CYP1A1 m1 16,41-52 and m2 16,42,44,46,[48][49][50][51][52][53][54][55] genotypes have been inconsistent.…”
mentioning
confidence: 99%